Sifat Kimia Tanah Bergambut dan Tanah Mineral Masam di Bawah Naungan Tanaman Kelapa Sawit - Robiansyah Robiansyah; Ahmad Kurnain; Ratna Ratna (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
An understanding of land suitability or management such as on peat and mineral soils in oil palm plantation areas is also very necessary as a basis for determining technical cultural actions to be taken in order to ensure the sustainability of the productivity of a land. This research was conducted with the aim of knowing the chemical properties of peat soils in Margasari Village, Candi Laras Utara District, Tapin Regency and mineral soils in Martadah Baru Village, Tambangulang District, Tanah Laut Regency under the auspices of oil palm plantations. The method used in this study was a quantitative descriptive method. The sampling point was determined by purposive sampling by showing the existing canopy in the field. Soil sampling in the field at a depth of 0-30 cm for each type of soil. This research plan is intended to describe soil pH, organic-C, total-N, and available-P. In general peat soils had quite high C-organic content values ​​compared to mineral soils. Changes in organic C affected the properties of the soil. The organic C content in all research locations was categorized as very low to medium, the soil pH is acidic, the total N content was moderate and the available P content was categorized as very low.